Posterolateral plate fixation with Pantalarlock® is more stable than nail fixation in tibiotalocalcaneal arthrodesis in a biomechanical cadaver study. Issue 3 (April 2020) - Gutteck, N.; Schilde, S.; Reichel, M.; Holtz, A.; Sahmel, O.; Hinz, P.; Kielstein, H.; Lange, J.; Delank, K.S.; Martin, H.
Highlights: The literature review failed to reveal any biomechanical analyses of the posterolateral plate in TTC arthrodesis. The objective of this work was a comparative biomechanical study of the posterolateral plate fixation with retrograde intramedullary nail fixation. We hypothesized that the plate fixation would provide higher primary stability in osteoporosis bone than nail. Abstract: Background: Despite the promising results of ankle joint arthroplasty, the tibiotalocalcaneal (TTC) arthrodesis remains an established procedure in treatment of combined pathology of the ankle and subtalar joint. Despite the promising results in biomechanical investigations, nonunion rates of up to 24% are described in recent studies. The objective of this work was a comparative study of the biomechanical properties of the posterolateral plate fixation with retrograde intramedullary nail fixation. Methods: Twenty four fresh-frozen human lower leg specimens (12 pairs) were used for the comparative biomechanical testing. Every specimen was preconditioned with 100 N over 200 cycles. After every 250 cycles the force was increased by 50 N from 200 to 600 N. This was followed by cyclic loading in dorsi-/plantiflexion with 800 N for 3000 cycles. All specimens were subjected to bone densitometry (DXA) and computed tomography. Results: Significantly higher number of spacimens with nails (4) failed during the cycling testing in dorsi-/plantarflexion and futher two during the cyclic testing with 800 N. Two specimens with plates failed during the cyclic testing with 800 N. Statistical analysis showed that the specimens with the plate were significantly more stable in each test direction. The Pearson correlation demonstrated for the specimens with plate a linear relationship between the stiffness and the determined bone density. Conclusions: The results demonstrate a significantly superior stiffness of the Pantalarlock®-plate in all testing directions compared with the HAN nail. Probably the position of the plate on the tension side of the joint and the combination of locking and lag screws provide the higher stiffness of the plate system. The correlation of the stiffness with bone density leads to more predictable results of the plate arthrodesis. We hope for a reduction of the pseudarthrosis rate and shorten the postoperative treatment phase. The authors expect advantages in the treatment of high risk patients with severe deformity of the ankle, bone defects, neuropathic deformity, poor bone quality and osteoporosis.